Suitable Friction Sliding Materials for Base Isolation of Masonry Buildings. (2012) - Nanda, Radhikesh P.; Agarwal, Pankaj; Shrikhande, Manish
Abstract : A feasibility study of friction base isolation system for seismic protection has been performed. Four different sliding interfaces, namely, green marble/High Density Poly Ethylene (HDPE), green marble/green marble, green marble/geosynthetic, and green marble/ rubber layers have been studied through experimental and analytical investigations. The experimental investigations show that the coefficient of friction values of these interfaces lies in the desirable range for seismic protection, i.e., 0.05 to 0.15. The analytical investigation reveals that most of these sliding interfaces are effective in reducing spectral accelerations up to 50% and the sliding displacement is restricted within plinth projection of 75 mm (3 in). Green marble and geosynthetic are found to be better alternatives for use in friction isolation system with equal effectiveness of energy dissipation and limiting the earthquake energy transmission to super structure during strong earthquake leading to a low cost, durable solution for earthquake protection of masonry buildings.